Tinjauan Pengaruh Strategi Penetapan Harga pada Pembelian Barang Melalui Bisnis Digital - Suherman, Geri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The study tested the price influence of the purchasing strategy of consumer goods. Also what was studied in this study was the influence of the internet (online presence) on informed purchasing decisions. The research is meant to answer the question of how much the price of a competitor affects the purchase of a product, how customers understand the concept of pricing based on the company's value, and how much online prices inform customer purchasing decisions. This paper is descriptive and historical and relies heavily on secondary sources of information. The findings from the data obtained suggest that consumers have a perception of value reflected in the price of the company's products. It also shows that the price of the competitor affects the purchase of the company's products and the online price informs and influences the purchase decision. This study contributes to knowledge on a range of issues related to price strategy and purchase decision-making processes. This research recommends that companies should focus on communicating customer value through price, companies should also pay attention to competitor prices and check how price affects their product purchase.